Complications of Liver Resection: Laparoscopic Versus Open Procedures - Slakey, Douglas P. (Society of Laparoendoscopic Surgeons, 2013)
BACKGROUND AND OBJECTIVE: Minimally invasive surgery for liver resection remains controversial. This study was designed to compare open versus laparoscopic surgical approaches to liver resection. METHODS: We performed a single-center retrospective chart review. RESULTS: We compared 45 laparoscopic liver resections with 17 open cases having equivalent resections based on anatomy and diagnosis. The overall complication rate was 25.8%. More open resection patients had complications (52.9% vs 15.5%, P < .008). The conversion rate was 11.1%. The mean blood loss was 667.1 ± 1450 mL in open cases versus 47.8 ± 89 mL in laparoscopic cases (P < .0001). Measures of intravenous narcotic use, intensive care unit length of stay, and hospital length of stay all favored the laparoscopic group. Patients were more likely to have complications or morbidity in the open resection group than in the laparoscopic group for both the anterolateral (P < .085) and posterosuperior (P < .002) resection subgroups. CONCLUSION: In this series comparing laparoscopic and open liver resections, there were fewer complications, more rapid recovery, and lower morbidity in the laparoscopic group, even for those resections involving the posterosuperior segments of the liver.